The Relationship Between Creativity and Intrusive Rumination Among Chinese Teenagers During the COVID-19 Pandemic: Emotional Resilience as a Moderator - Wang, Qian; Zhao, Xin; Yuan, Yuming; Shi, Baoguo (Frontiers in Psychology, 2021)
Coronavirus disease 2019 (COVID-19) has not only resulted in immeasurable life and property losses worldwide but has also impacted individuals’ development, especially teenagers. After the COVID-19 pandemic, individual rumination as an important cognitive process should be given more attention because of its close associations with physical and mental health. Previous studies have shown that creativity as an antecedent variable can predict people’s mental health or adaptation. However, few studies have focused on the relationship between creativity and individual cognitive rumination after traumatic events, and the mechanism underlying this relationship remains unclear. By using the Runco Ideational Behavior Scale (RIBS), the Event Related Rumination Inventory, and the Questionnaire of Adolescent Emotional Resilience, the current study explored the relationship between creativity and intrusive rumination among 1488 Chinese teenagers during the COVID-19 pandemic and analyzed the moderating effect of emotional resilience on the relationship. The results showed that creativity, as assessed by the RIBS, was positively related to teenagers’ intrusive rumination, which implied that a higher level of creative performance could predict more intrusive rumination. Moreover, emotional resilience acted as a moderator in the relationship between creativity and intrusive rumination; the correlation was stronger when emotional resilience was low. These findings provide more evidence of the relationship between creativity and mental health and show the effect of this traumatic event on teenagers.